2018
DOI: 10.1016/j.wocn.2018.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Training-induced pattern-specific phonetic adjustments by first and second language listeners

Abstract: The current study investigated the phonetic adjustment mechanisms that underlie perceptual adaptation in first and second language (Dutch-English) listeners by exposing them to a novel English accent containing controlled deviations from the standard accent (e.g. /i/-to-/ɪ/ yielding /krɪm/ instead of /krim/ for ‘cream’). These deviations involved contrasts that either were contrastive or were not contrastive in Dutch. Following accent exposure with disambiguating feedback, listeners completed lexical decision … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 47 publications
(70 reference statements)
3
11
0
Order By: Relevance
“…For participants to change their phonemic boundaries on the basis of just 16 critical accented words in the Code Breaker game thus requires a substantial amount of pretest exposure to be unlearned. Strengthening the evidence for the vowel shift during the interactive game-whether by increasing the number of critical trials or by incorporating additional accented vowels to form a chain shift as in [7] and [8]-would probably increase the lexically driven adaptation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For participants to change their phonemic boundaries on the basis of just 16 critical accented words in the Code Breaker game thus requires a substantial amount of pretest exposure to be unlearned. Strengthening the evidence for the vowel shift during the interactive game-whether by increasing the number of critical trials or by incorporating additional accented vowels to form a chain shift as in [7] and [8]-would probably increase the lexically driven adaptation.…”
Section: Discussionmentioning
confidence: 99%
“…As for a full vowel shift, one study showed that English listeners exposed to 20 minutes of synthesized speech with systematic front vowel lowering adapted their lexical decision judgments in accordance with the vowel change [7]. Another study showed that both Dutch and native English listeners adapted to a series of lowered front vowel shifts heard in 72 training items in a manipulated English accent [8]. Whether adaptation to a vowel shift can also occur with more limited exposure than in [7] and [8], given the relative instability of the perceptual adaptation in [6], remains to be seen.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, crosslinguistic constraints on L2 perceptual learning have also been observed. For instance, Cooper and Bradlow (2018) showed that after exposure to accented English words presented in a lexically or semantically disambiguating context, Dutch listeners exhibited perceptual adaptation for words containing the trained accent pattern, but only for deviations involving phoneme pairs that were contrastive in both the L1 and L2.…”
Section: Implicit Perceptual Learning Through Lexical Guidancementioning
confidence: 99%
“…Nonnative speech learning provides another case in which rapid learning is reduced when speech perception is heavily challenged (Banai & Lavner, 2016;Cooper & Bradlow, 2018;Perrachione, Lee, Ha, & Wong, 2011). The perceptual difficulties of nonnative listeners under challenging listening situations are well documented (for review, see Lecumberri, Cooke, & Cutler, 2010).…”
Section: Rapid Perceptual Learning Seems Reduced In Groups With Speech Perception Difficultiesmentioning
confidence: 99%